Binder‐Free and High‐Loading Cathode Realized by Hierarchical Structure for Potassium–Sulfur Batteries. Issue 1 (4th December 2021) - Yang, Kaiwei; Kim, Soochan; Yang, Xin; Cho, Misuk; Lee, Youngkwan
Abstract: Potassium–sulfur batteries have attracted significant research attention owing to the naturally abundant resources of potassium and sulfur, and have promising applications in large‐scale energy storage systems. However, the sluggish reaction kinetics of K +, low reaction activity of sulfur species, shuttling effect of polysulfides, and large volume change impede the development of these batteries. Moreover, the conventional electrode fabrication method with binders and current collectors renders it difficult to improve the areal sulfur loading and energy density. In this study, a binder‐free and freestanding sulfur cathode is prepared by phase inversion and sulfurization of polyacrylonitrile. This sulfur cathode, with a hierarchically porous network, enables a high reversible capacity of 1345 mAh g −1 and a stable cycling performance with a capacity decay of 0.15% per cycle. Importantly, areal capacities of 3.1 and 4.2 mAh cm −2 are achieved even at high sulfur loadings of 3 and 7 mg cm −2, owing to the favorable electron/ion transport in the cathode. The facile preparation method and excellent electrochemical properties reported herein can pave the way for developing high‐performance K‐S batteries. Abstract : A binder‐free and high‐loading sulfur cathode is developed via facile phase inversion and sulfurization for application in potassium–sulfur batteries without using a current collector. The hierarchical structure of the cathode enables favorable ionic transport; therefore, a high areal capacity is successfully exerted even at high loadings. Moreover, the porous structure buffers the volume change, and good cycling stability is achieved.